Evaluating the Role of Homoeopathic Constitutional Treatment in the Management of Gastroesophageal Reflux Disease (GERD): An Experimental Study - Gavhane, Ganesh Dhanu; Tupe, Sharmila; Dusane, Mahesh; Gavhane, Priyanka Ganesh; gangwar, Vandana; Kanupriya, Kanupriya (Journal of Neonatal Surgery, 2025)
Gastroesophageal reflux disease (GERD) is a widespread chronic condition that significantly affects quality of life through symptoms such as heartburn, regurgitation, and sleep disturbances. Conventional therapies, though effective in symptom control, often fail to address the root cause and may lead to side effects. This study explores the efficacy of individualized homoeopathic constitutional treatment in managing GERD. Thirty patients were enrolled and treated over six months, with symptom severity measured using the FSSG scale. The findings revealed statistically significant improvement in symptoms and quality of life, suggesting that homoeopathic intervention may offer a viable alternative for GERD management